2016
DOI: 10.19071/jpsp.2016.v2.3076
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Stress Induced Antioxidative and Biochemical Changes in Wheat (Triticum aestivum L.) Cultivars

Abstract: The aim of this study is to understand the effect of elevated temperature on wheat seedlings of four cultivars, gayetri (GY), gandhari (GN), kedar (KD), PBW343 in terms of tolerance/susceptibility, along with antioxidative and biochemical responses. For this, seedlings of four cultivars were exposed to different temperatures ranging from 25°C to 40°C for 6 h. According to heat susceptibility index calculated, GN was found to be heat tolerant, PBW343 heat sensitive, and the other two, GY and KD moderately toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…The reduced Chl content under heat stress could be explained by the reduced expression of Chl synthase (CS) gene as reported by Saha et al (2016) for the C4 plant species Setaria viridis. Similar to our observations in barley, the reduced Car under heat stress (at temperatures above 35 o C) was reported for bread wheat (Sarkar et al 2016) and durum wheat (Dias et al 2011). The high correlation observed between Chl content and PN under high temperatures may be caused by both the downregulation of Chl synthesis in the chloroplast and the accumulation of reactive oxygen species, which lead to Chl degradation in plants and the subsequently reduced PN (Dwivedi et al 2017).…”
Section: Discussionsupporting
confidence: 89%
“…The reduced Chl content under heat stress could be explained by the reduced expression of Chl synthase (CS) gene as reported by Saha et al (2016) for the C4 plant species Setaria viridis. Similar to our observations in barley, the reduced Car under heat stress (at temperatures above 35 o C) was reported for bread wheat (Sarkar et al 2016) and durum wheat (Dias et al 2011). The high correlation observed between Chl content and PN under high temperatures may be caused by both the downregulation of Chl synthesis in the chloroplast and the accumulation of reactive oxygen species, which lead to Chl degradation in plants and the subsequently reduced PN (Dwivedi et al 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, according to authors, in young leaves of model system plant Chenopodium album increased SOD activity was followed by loss in leaf soluble protein content, whereas for a single CAT isozyme optimal temperature and stability is required, considering that the activity was showed only at up to 40 • C. This is in agreement with our results for young basil leaves under high temperature stress, which caused loss in leaf soluble proteins, induced SOD and A-POX activity for both heat-stress temperatures, and induced CAT activity only for 30 • C, while for 40 • C the activity of CAT decreased. To the best of our knowledge, there are no reports of antioxidant enzyme activity in basil under the heat stress conditions; however, our results are in accordance with previous research where heat stress caused the higher activity of SOD in 'Carrizo' citrange [36], and CAT and peroxidases in wheat genotypes [37] under 40 and 30 • C, respectively. Furthermore, as proved by statistical analysis, under the conditions of temperature stress significant positive correlation was found between various antioxidant enzymes and chlorophyll content, which is in accordance with the results of Almeselmani et al [19].…”
Section: Discussionsupporting
confidence: 92%
“…Liu et al [93] reported decreased SOD and CAT activities with corresponding suppressed OsSOD, OsCAT, and OsAPX2 expression, resulting in higher accumulation of H 2 O 2 (1.27-fold) in germinating rice seeds under HT stress. Sarkar et al [198] found elevated activity of CAT and POX in wheat genotypes under HT stress (30 • C). In another example, Zandalinas et al [199] observed increased GSH and AsA content in Carrizo citrange along with enhanced SOD and CAT activity compared with Cleopatra mandarin under HT stress (40 • C).…”
Section: Antioxidant Defense In Plants Under High Temperaturementioning
confidence: 99%